2001
DOI: 10.1074/jbc.m101815200
|View full text |Cite
|
Sign up to set email alerts
|

Specific Interaction of Angiostatin with Integrin αvβ3 in Endothelial Cells

Abstract: Angiostatin, the N-terminal four kringles (K1-4) of plasminogen, blocks tumor-mediated angiogenesis and has great therapeutic potential. However, angiostatin's mechanism of anti-angiogenic action is unclear. We found that bovine arterial endothelial (BAE) cells adhere to angiostatin in an integrin-dependent manner and that integrins ␣ v ␤ 3 , ␣ 9 ␤ 1 , and to a lesser extent ␣ 4 ␤ 1 , specifically bind to angiostatin. ␣ v ␤ 3 is a predominant receptor for angiostatin on BAE cells, since a functionblocking anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
127
1
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(147 citation statements)
references
References 57 publications
14
127
1
5
Order By: Relevance
“…This has been demonstrated for endostatin (Rehn et al, 2001), angiostatin (Tarui et al, 2001), thrombospondin-1 (for a review, see Bornstein, 2001) and tumstatin (Maeshima et al, 2000). Indeed, when molecules such as angiostatin Mauceri et al, 1998), endostatin (Hanna et al, 2000) or neutralising anti-human VEGF 165 antibodies (Gorski et al, 1999;Lee et al, 2000) are administered together with ionising radiation, the cytotoxic effects of the latter upon endothelial cells are potentiated in vivo, resulting in an enhanced antitumoral effect.…”
Section: Discussionmentioning
confidence: 74%
“…This has been demonstrated for endostatin (Rehn et al, 2001), angiostatin (Tarui et al, 2001), thrombospondin-1 (for a review, see Bornstein, 2001) and tumstatin (Maeshima et al, 2000). Indeed, when molecules such as angiostatin Mauceri et al, 1998), endostatin (Hanna et al, 2000) or neutralising anti-human VEGF 165 antibodies (Gorski et al, 1999;Lee et al, 2000) are administered together with ionising radiation, the cytotoxic effects of the latter upon endothelial cells are potentiated in vivo, resulting in an enhanced antitumoral effect.…”
Section: Discussionmentioning
confidence: 74%
“…Takada's group investigated bovine arterial endothelial (BAE) cell binding to a variety of proteins, including angiostatin, coated onto plastic microtiter plates [Tarui et al, 2001]. They found that BAE cells bound to angiostatin in a dose-and magnesium-dependent manner, and that binding was saturable at approximately 200 nM angiostatin.…”
Section: Cell Surface Target: Angiomotinmentioning
confidence: 99%
“…A potential criticism of the Tarui et al [2001] study is that the molecular basis of angiostatinintegrin interactions remains completely uncharacterized. We note that there are no RGD motifs found in either human or mouse plasminogen/angiostatin sequences, although other sequences could be involved.…”
Section: Cell Surface Target: Angiomotinmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to angiostatin's ability to alter neutrophil trafficking 34 or adhesion molecule expression on endothelial cells. Angiostatin, when bound to integrins, 35 may alter trafficking of lymphocytes, while the expression of hypoxic-induced proangiogenic factors in tumors can alter the expression of cell adhesion molecules involved in systemic cell trafficking. 36,37 Hence, this alteration by angiostatin in the trafficking of cells that have receptors for IL-2 may affect how IL-2 is distributed throughout the host.…”
Section: Discussionmentioning
confidence: 99%